Problem stosowania używek wśród seniorów mieszkających w środowisku domowym = The problem of the use of drugs among seniors living in the home environment - Bartoszek, Agnieszka; Kocka, Katarzyna; Zielonka, Edyta; Łuczyk, Marta; Rząca, Marcin; Deluga, Alina; Domżał-Drzewicka, Renata; Szadowska-Szlachetka, Zdzisława (Journal of Education, Health and Sport, 2016)
Bartoszek Agnieszka, Kocka Katarzyna, Zielonka Edyta, Łuczyk Marta, Rząca Marcin, Deluga Alina, Domżał-Drzewicka Renata, Szadowska-Szlachetka Zdzisława. Problem stosowania używek wśród seniorów mieszkających w środowisku domowym = The problem of the use of drugs among seniors living in the home environment. Journal of Education, Health and Sport. 2016;6(6):235-244. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.55180 http://ojs.ukw.edu.pl/index.php/johs/article/view/3572 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.05.2016. Revised 25.05.2016. Accepted: 10.06.2016. Problem stosowania używek wśród seniorów mieszkających w środowisku domowym The problem of the use of drugs among seniors living in the home environment Agnieszka Bartoszek1, Katarzyna Kocka1, Edyta Zielonka2, Marta Łuczyk3, Marcin Rząca3, Alina Deluga1, Renata Domżał‑Drzewicka1, Zdzisława Szadowska‑Szlachetka3 1Zakład Medycyny Rodzinnej i Pielęgniarstwa Środowiskowego, Katedra Onkologii i Środowiskowej Opieki Zdrowotnej, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie 2Oddział Kardiologii, Wojewódzki Szpital Specjalistyczny im. Stefana Kardynała Wyszyńskiego w Lublinie 3Zakład Onkologii, Katedra Onkologii i Środowiskowej Opieki Zdrowotnej, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie Słowa kluczowe: seniorzy, używki, środowisko domowe. Key words: seniors, drugs, home environment. Abstrakt Wprowadzenie Przebieg procesu starzenia uzależniony jest od prezentowanych przez całe życie zachowań zdrowotnych i stylu życia. Wśród tych zachowań często kontynuowanych w procesie starzenia istotne miejsce zajmują nałogi palenia papierosów i spożycia alkoholu Cel pracy rozpoznanie częstości stosowania używek typu palenie papierosów i spożycie alkoholu wśród seniorów oraz określenie czynników różnicujących ich występowanie Materiał i metoda Badaniem objęto 110 osób starszych mieszkających w województwie lubelskim Do zbierania informacji wykorzystano autorski kwestionariusz ankiety. Przyjęto poziom istotności p<0,05. Wyniki Do kontaktu z tytoniem przyznaje się 29,1% seniorów. Seniorzy w przeważającej większości (83,6%) po alkohol sięgają okazjonalnie. Palenie tytoniu częściej dotyczy mężczyzn (48,2%) niż kobiet (8,9%), podobnie jak konsumpcja alkoholu: mężczyźni (29.6 %), kobiety (3.6%). W grupie osób po 75 roku życia palacze stanowią 37,5%, natomiast w wieku 65-74 lata jest to 18,5% respondentów. Częściej palą tytoń mieszkańcy wsi (36,8%) niż miast 18,9%. Konsumpcja alkoholu częściej dotyczy osób ze środowisk wiejskich (24,6%), niż miejskich (7,5%). Większość pijących alkohol ma wykształcenie podstawowe (38.2%). Spożywanie alkoholu jest bardziej charakterystyczne dla osób stanu wolnego (27,8%) niż pozostających w związkach (10,8%). Wnioski Wśród palaczy stanowiących 1/3 badanych dominują osoby po 75 r.ż., mężczyźni, osoby pochodzące ze środowisk wiejskich. Seniorzy pijący alkohol to najczęściej mężczyźni, osoby stanu wolnego, mieszkające na wsi, i z wykształceniem podstawowym. Abstract Background The aging process is dependent of presented by a lifelong health behaviours. Among these behaviours, often continued during the aging process, an important place occupy the habits of cigarette smoking and alcohol consumption. Objective Recognizing the incidence of cigarette smoking and alcohol consumption among seniors, also identify the factors that differentiate their occurrence. Material and methods The study involved 110 elderly people over 65 years of age, living in Lublin province . To collect information used original questionnaire. The level of significance p < 0.05. Results To contact with tobacco admit 29.1 % of seniors . The overwhelming majority (83.6 %) of seniors consume alcohol occasionally. Cigarette smoking applies especially men (48.2%) than women (8.9%) , same as alcohol consumption: men ( 29.6 % ), women ( 3.6%) . In the group of people over 75 years of age, smokers constitutes 37.5%, of 65-74 years old - 18.5 % of respondents. Rural residents (36.8 %) smoke the cigarettes more often than urban residents (18.9%). Alcohol consumption is also more frequently in rural areas (24.6 %) than in the cities (7.5%). The most people who consume alcohol have a basic education (38.2%). Alcohol consumption applies mostly unmarried people (27.8 %) than people who are in relationship (10.8 % ). Conclusions Among 1/3 respondents – smokers, dominate people over 75 years of age. Those are men, living in rural areas. Seniors who consume alcohol are mostly single men, living in rural ares and also having basic education.